Conditional survival analysis of hepatocellular carcinoma. Issue 4 (10th June 2020) - Shah, Mihir M.; Meyer, Benjamin I.; Rhee, Kevin; NeMoyer, Rachel E.; Lin, Yong; Tzeng, Ching‐Wei D.; Jabbour, Salma K.; Kennedy, Timothy J.; Nosher, John L.; Kooby, David A.; Maithel, Shishir K.; Carpizo, Darren R.
Abstract: Background: Hepatocellular carcinoma (HCC) is a leading cause of cancer‐related mortality worldwide with an approximate 5‐year survival of greater than 50% in patients after surgical resection. Survival estimates have limited utility for patients who have survived several years after initial treatment. We analyzed how conditional survival (CS) after curative‐intent surgery for HCC predicts survival estimates over time. Methods: NCDB (2004‐2014) was queried for patients undergoing definitive surgical resection for HCC. Cumulative overall survival (OS) was calculated using the Kaplan‐Meier method, and CS at x years after diagnosis was calculated as CS1  = OS ( X +5) /OS( X ) . Results: The final analysis encompassed 11 357 patients. Age, negative margin status, grade severity and radiation before surgery were statistically significant predictors of cumulative overall conditional survival ( P  ≤ .0001). Overall unconditional 5‐year survival was 65.7%, but CS estimates were higher. A patient who has already survived 3 years has an additional 2‐year, or 5‐year CS, estimate of 86.96%. Conclusion: Survival estimates following hepatic resection in HCC patients change according to survival time accrued since surgery. CS estimates are improved relative to unconditional OS. The impact of different variables influencing OS is likewise nonlinear over the course of time after surgery.